Funciones ejecutivas: razonamiento en los estudiantes de la Facultad de Ciencias de la Educación, Humanas y Tecnologías de la Universidad Nacional de Chimborazo - Villacrés Lara, Angel Fernando (2021)
The main objective of this research was to determine the level of development of Executive Functions: reasoning in students of the fifth semester of the Psychopedagogy, Pedagogy, Mathematics and Physics careers in the Faculty of Human Sciences and Technologies at the National University of Chimborazo. This problem was relevant in the educational field, since Executive Functions are a series of higher cognitive capacities that allow the channeling of information, planning, decision-making and control of emotions. Students with difficulties in these processes often understand complex concepts, but they must do more to show what they know due to the difficulty in planning, prioritizing goals to organize materials and information. The methodology correspond to a quantitative approach, its design was non-experimental, its level was descriptive, the type of research by objective was basic, for the time it was cross-sectional, for the place it was field, the sample was taken to the students from the aforementioned institution, the sample was intentional non-probabilistic since it worked with 46 students, the technique used was: the application of the psychometric battery "Raven's Progressive Matrices", which was a source of great help in obtaining and collecting data and results.Keywords: Parental socialization, Adolescents, Dimesions, Socialization style, Parents.